2003
DOI: 10.1300/j045v17n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction

Abstract: African American women are less likely than other groups of women to use health care services despite an equal or greater need. In particular, they may rely more frequently on informal sources of health care advice, such as family members and/or social support networks. Very little is known about how African American women view the health care system because few studies have investigated the impact of race and gender on patient satisfaction. To address this gap, we analyzed transcripts of focus groups conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Consistent with previous research (Christen, et al, 2008; Copeland, Scholle, & Binko, 2003; Howell, et al, 2002; Mavis, Vasilenko, Schnuth, Marshall, & Colavito, 2005), verbal and nonverbal communication were critical to a successful client-provider interaction. English speaking ability of non-native providers was of primary concern.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with previous research (Christen, et al, 2008; Copeland, Scholle, & Binko, 2003; Howell, et al, 2002; Mavis, Vasilenko, Schnuth, Marshall, & Colavito, 2005), verbal and nonverbal communication were critical to a successful client-provider interaction. English speaking ability of non-native providers was of primary concern.…”
Section: Discussionsupporting
confidence: 83%
“…Handler, Rosenberg, Raube, and Lyons (2003) found that African American women were more satisfied with prenatal care when providers engaged them by asking and answering questions, explaining procedures, and spending more time with them. Other studies on what women expect from providers have been completed but have not focused on pregnant African American women (Carr-Copeland, Hudson-Scholle, & Binko, 2003; Houle, Harwood, Watkins, & Baum, 2007) or reported the race of the pregnant women (Douglas, Cervin, & Bower, 2007). Given the opportunity that prenatal care presents to intervene with pregnant women, it is important to examine the qualities desired in a prenatal provider in order to improve the patient–provider relationship and overall quality of prenatal care.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…With regard to cancer screening behaviors, family networks are associated with both recent cancer screening and the intention to screen for cancer [11]. In addition, African Americans often rely on informal sources of health care advice such as family members and church based support [12], suggesting a potential influence on treatment adherence particularly among a survivor group that has reported difficulty talking about the disease [13]. …”
Section: Introductionmentioning
confidence: 99%